Banking sector performance in some Latin American countries: Market power versus efficiency - Georgios E. Chortareas; Jesus Gustavo Garza-Garcia; Claudia Girardone (Banco de México, 2010)
The wave of consolidation and the rapid increase in market concentration that took place in most Latin American countries has generated concerns about the rise in banks' market power and its potential effects on consumers. This paper advances the existing literature by testing the market power (Structure-Conduct-Performance and Relative Market Power) and efficient structure (X- and scale effciency) hypotheses for a sample of over 2,500 bank observations in nine Latin American countries over 1997-2005. We use the Data Envelopment Analysis technique to obtain reliable efficiency measures. We produce evidence supporting the efficient structure hypotheses. Finally, capital ratios and bank size seem to be among the most important factors in explaining profits for these Latin American banks.
Keywords: G21; D24; 330; Structure-Conduct-Performance; Efficient Structure; Banking System in Some Latin American Countries; Data Envelopment Analysis (DEA); Bank; Data-Envelopment-Analyse; Struktur-Performance-Modell; Marktmacht; X-Effizienz; Lateinamerika